The impact of women’s economic empowerment on human development in sub-Saharan Africa: A panel quantile regression approach - Mekhzoumi, Lotfi; Chikh-Amnache, Sabrina; Mekhzoumi, Nabila (Economics and Business Review, 2025)
This paper uses a panel quantile regression approach to study the economic empowerment of women in sub-Saharan Africa and how it impacts human development. Analysing data collected from 42 countries covering the period 2000–2023, the study looks at various indicators of women’s economic empowerment. The impacts of women’s economic empowerment are found to differ depending on quantile levels; female entrepreneurship shows a significant impact only at higher levels. Across all levels, marriage rights and workplace participation repeatedly show positive impacts. The Gender Development Index’s significant positive impact underscores the importance of gender equality for overall human development. Parenting rights and mobility show positive results at most levels, though there are some variations.